2020
DOI: 10.3389/fpls.2020.00896
|View full text |Cite
|
Sign up to set email alerts
|

Flavescence Dorée-Derived Leaf Yellowing in Grapevine (Vitis vinifera L.) Is Associated to a General Repression of Isoprenoid Biosynthetic Pathways

Abstract: Overall, results indicated that the FD infection impairs the synthesis of isoprenoids, through the repression of key genes involved in the biosynthesis of chlorophylls, carotenoids, quinones and tocopherols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 79 publications
(101 reference statements)
1
18
0
Order By: Relevance
“…Pearson correlations were calculated using MetScape plugin from Cytoscape version 3.8.2 () from a matrix of metabolite and transcript values of grape berries and leaves normalized on green stage values (Supplementary Table 2), as reported by Diretto et al (2010) and Teixeira et al. (2020) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pearson correlations were calculated using MetScape plugin from Cytoscape version 3.8.2 () from a matrix of metabolite and transcript values of grape berries and leaves normalized on green stage values (Supplementary Table 2), as reported by Diretto et al (2010) and Teixeira et al. (2020) …”
Section: Methodsmentioning
confidence: 99%
“…Pearson correlations were calculated using MetScape plugin from Cytoscape version 3.8.2 (www.cytoscape.org) from a matrix of metabolite and transcript values of grape berries and leaves normalized on green stage values (Supplementary Table 2), as reported by Diretto et al (2010) 37 and Teixeira et al (2020). 38 The network diagram was generated with Pearson correlation values (ρ ≥ 0.90 and ρ ≤ −0.90) using a compound profuse force directed layout algorithm. Node strength (ns) calculation, intended as the average of all of the |ρs| yielded by each node, was used to identify the main elements ("hubs") of the network (Supplementary Table 2).…”
Section: Metabolomics Analysismentioning
confidence: 99%
“…Correlations between yeast species were assembled using the MetScape plugin from Cytoscape version 3.8.1 (www. cytoscape.org; Cline et al, 2007), according to their overall response to all tested elicitors, normalised to the respective control without treatment (Teixeira et al, 2020). In the network diagram, generated using a perfuse force direct layout algorithm, node size is proportional to the correlation node strength.…”
Section: Network Analysismentioning
confidence: 99%
“…Positive (ρ > 0.10) and negative (ρ < -0.10) correlations were coloured in red and blue, respectively. MCODE plugin was used to obtain a series of metrical topological parameters of the network, allowing, on a mathematical basis, to unravel the denser areas and distinguish the subnetworks with strong cross-links (Teixeira et al, 2020).…”
Section: Network Analysismentioning
confidence: 99%
“…Different studies have reported harmful effects of the infection at both physiological and molecular levels, revealing modifications in the primary and secondary metabolism. This is the case of the isoprenoid biosynthetic pathways, which are repressed in response to infection, accounting for leaf yellowing, which is a hallmark of the disease (Teixeira et al, 2020). Other studies have revealed that the accumulation of sucrose and starch in the leaf mesophyll is accompanied by the up-regulation of key genes involved in their synthesis, including Sucrose synthase 4 (VvSusy4) (Hren et al, 2009;Margaria et al, 2014;Prezelj et al, 2016).…”
Section: Introductionmentioning
confidence: 99%